Early Detection of Vulnerable Atherosclerotic Plaque for Risk Reduction of Acute Aortic Rupture and Thromboemboli and Atheroemboli Using Non-Obstructive Angioscopy - Yutani, Chikao; Hirayama, Atsushi; Komatsu, Sei; Ohara, Tomoki; Minamiguchi, Hitoshi; Imai, Atsuko; Iwa, Nobuzo; Kodama, Kazuhisa; Kobayashi, Yasuhiko; Takahashi, Satoru; Takewa, Mitsuhiko (Circulation Journal, 2015)
The mortality rate due to rupture of aortic dissection and aortic aneurysm is approximately 90%. Acute aortic rupture can be fatal prior to hospitalization and has proven difficult to diagnose correctly or predict. The in-hospital mortality rate of ruptured aortic aneurysm ranges from 53 to 66%. Emergency surgical and endovascular treatments are the only options for ruptured aortic dissection and aortic aneurysm. No method of systematic early detection or inspection of vessel injury is available at the prevention stage. Regardless of the improvement in many imaging modalities, aortic diameter has remained a major criterion for recommending surgery in diagnosed patients. Previous reports have suggested a relationship between vulnerable plaque and atherosclerotic aortic aneurysm. Non-obstructive angioscopy is a new method for evaluating intimal injury over the whole aorta. It has been used to identify many advanced atherosclerotic plaques that were missed on traditional imaging modalities before aneurysm formation. Non-obstructive angioscopy has shown that atherosclerosis of the aorta begins before that of the coronary artery, which had been noted on autopsy “in vivo”. Strong or repetitive aortic injuries might cause sudden aortic disruption. Aortic atheroma is also a risk factor of stroke and perivascular embolism. Detecting aortic vulnerable atherosclerotic plaque on non-obstructive angioscopy may not only clarify the pathogenesis of acute aortic rupture and “aortogenic” thromboemboli and atheroemboli but also play a role in the pre-emptive medicine. (Circ J 2015; 79: 742–750)